Quin Franciscan Friary, cloister, capital - O'Donovan, Danielle; O'Donoghue, Aisling (My University, 2008)
Cloister capital, moulding from top down comprises: roll, flat surface, scroll, fillet, bell, necking roll.
Cloister
Keywords: scroll; Architecture, Gothic -- Ireland; Quin Abbey; Architecture, Franciscan; Cloisters (Architecture); Gothic capitals (Architecture); Late Medieval; roll moldings; fillets (moldings); bell capitals